2016
DOI: 10.5194/acp-16-8423-2016
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of aerosol indirect effects on monsoon clouds using ground-based measurements over a high-altitude site in Western Ghats

Abstract: Abstract. The effect of aerosols on cloud droplet number concentration and droplet effective radius is investigated from ground-based measurements over a high-altitude site where clouds pass over the surface. First aerosol indirect effect (AIE) estimates were made using (i) relative changes in cloud droplet number concentration (AIE n ) and (ii) relative changes in droplet effective radius (AIE s ) with relative changes in aerosol for different cloud liquid water contents (LWCs). AIE estimates from two differe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…One of the key factors in the cloud microphysics parameterizations is relative dispersion ( ε ), defined as the ratio of standard deviation of droplet radius to mean droplet radius of droplet size distributions. It is well known that ε has significant influences on aerosol indirect effect evaluation, warm‐rain initiation, cloud‐climate feedbacks, through its effects on cloud effective radius, cloud optical depth (Anil Kumar et al, 2016; McComiskey et al, 2009; Peng et al, 2007; Tas et al, 2012; Wang et al, 2011; Wang et al, 2013; Zhao et al, 2006; Zhao et al, 2019), and autoconversion processes (Liu et al, 2004; Liu et al, 2006; Liu et al, 2007; Lu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One of the key factors in the cloud microphysics parameterizations is relative dispersion ( ε ), defined as the ratio of standard deviation of droplet radius to mean droplet radius of droplet size distributions. It is well known that ε has significant influences on aerosol indirect effect evaluation, warm‐rain initiation, cloud‐climate feedbacks, through its effects on cloud effective radius, cloud optical depth (Anil Kumar et al, 2016; McComiskey et al, 2009; Peng et al, 2007; Tas et al, 2012; Wang et al, 2011; Wang et al, 2013; Zhao et al, 2006; Zhao et al, 2019), and autoconversion processes (Liu et al, 2004; Liu et al, 2006; Liu et al, 2007; Lu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is to note that the biological aerosols can act as both ice nuclei and GCCN, and thus, their effect could be very important in cloud and rain processes. The study site, WGs, is rich in vegetation and thus acts as a source for organic and biological aerosols (e.g., pollen, lichen, bacteria, and leaf fragments) (Anil Kumar et al, ). Thus, the presence of GCCN like sea salt along with other organic and biological aerosols are more effective in modifying the intensity and amount of precipitation in clouds with bigger drop size and higher terminal velocity.…”
Section: Resultsmentioning
confidence: 99%
“…Entrainment in cumulus is primarily lateral with strong dilution of the cloud, which induces LWC to decrease rapidly to approximately 20 % of its adiabatic value (Warner, 1955). Entrainment in stratocumulus is mainly determined by the strength of the gradients in buoyancy and horizon-tal winds (Wang and Albrecht 1994;Gerber et al, 2005;de Roode and Wang 2007;Wood, 2012) and proceeds from the top and mostly affects a thin layer (Gerber et al, 2005), whose dilution effect is much weaker than that in cumulus (Warner, 1955(Warner, , 1969aBlyth et al, 1988;Gerber et al, 2008;Burnet and Brenguier, 2007;Haman et al, 2007). Aircraft observations of marine stratocumulus clouds showed that the vertical profile of LWC is essentially the same as the adiabatic profile; i.e., the cloud is almost adiabatic (Keil and Haywood, 2003).…”
Section: Entrainment In Stratocumulusmentioning
confidence: 99%